Delirium and topographical disorientation associated with glioblastoma multiforme tumour progression into the isthmus of the cingulate gyrus. (17th August 2018) - Zervos, Thomas M; Robin, Adam M; Lee, Ian
Abstract : Since there is no cure for glioblastoma multiforme (GBM), the goal of treatment becomes prolonging the survival through cytoreduction while minimising neurological deficits. In this case report, laser interstitial thermal therapy (LITT) was used once the tumour progressed into the isthmus of the cingulate gyrus. One year after temporal lobectomy, disorders of memory, emotion, personality and navigation, likely related to limbic system involvement along with hallucinations and fluctuating cognition occurred as the tumour progressed. After ablation of the posterior cingulum, worsening of topographical disorientation was observed. Per literature review, delirium has been noted in patients with strokes involving the right-sided temporo-parieto-occipital junction, and topographical disorientation has been associated with lesions of the right posterior cingulum. Alternative causes of these deficits were ruled out, leaving structural changes as the primary explanation. This is the first report of the neurological deficits associated with tumour progression and vasogenic oedema in this region.